Jung on death and immortality - Jung, C. G. (Carl Gustav), 1875-1961 (Jung, C. G. (Carl Gustav), 1875-1961. Works. 1995., 1999)
"As a doctor, I make every effort to strengthen the belief in immortality, especially with older patients when such questions come threateningly close. For, seen in correct psychological perspective, death is not an end but a goal, and life's inclination towards death begins as soon as the meridian is past."--C.G. Jung, commentary on The Secret of the Golden Flower ? Here collected for the first time are Jung's views on death and immortality, his writings often coinciding with the death of the most significant people in his life. The book shows many of the major themes running throughout the writings, including the relativity of space and time surrounding death, the link between transference and death, and the archetypes shared among the world's religions at the depths of the Self. The book includes selections from "On Resurrection," "The Soul and Death," "Concerning Rebirth," "Psychological Commentary on The Tibetan Book of the Dead" from the Collected Works, "Letter to Pastor Pfafflin" from Letters, and "On Life after Death."